Analysis of Factors Affecting Service Quality at the Anggeraja Community Health Center - Herman H Herman H; Muhammad Irvan Nur' Iva; Andi Asrifan; Waode fitri noviana Putri; Japaruddin; Zumarina (Journal of Political and Governance Studies, 2025)
Background The quality of service at the Community Health Center plays an important role in increasing patient satisfaction and the health status of the community. This study aims to analyze the factors that influence service quality at the Anggeraja Community Health Center Method The research used a descriptive qualitative approach with informants consisting of the head of the community health center, healthcare workers, administrative staff, and patients. Data collection techniques include in-depth interviews, direct observation, and document studies. Result The research results indicate that service quality is influenced by driving factors such as the competence of healthcare workers, service management, staff attitudes and communication, as well as facilities and infrastructure. Factors that hinder progress include government support, budget allocation, and supporting facilities. Some of the obstacles found include a shortage of healthcare workers, high workload, limited facilities, long operational service standards, and suboptimal cross-program coordination. Conclusion This research confirms that the combination of inhibiting and driving factors is crucial in determining service quality. Quality improvement efforts can be achieved through stunting prevention training, optimization of facilities and infrastructure, use of a manual queuing system, improved management, and consistent government support. This finding is expected to serve as a basis for recommendations to improve the quality of service at Anggeraja Health Center and other health centers.